2017
DOI: 10.1002/job.2259
|View full text |Cite
|
Sign up to set email alerts
|

Examining the nature, causes, and consequences of profiles of organizational citizenship behavior

Abstract: Summary Research on organizational citizenship behavior (OCB) typically focuses on either one type of OCB or an aggregate of multiple types of OCB. We investigate a third conceptualization of OCB by examining how employees use conscientiousness, sportsmanship, civic virtue, courtesy, and altruism in distinct combinations. In Study 1, we identify 5 profiles of citizenship in a sample of 129 workers in a medium‐sized firm. Some employees used either high levels (prosocial citizens), above average levels (contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 97 publications
4
85
1
6
Order By: Relevance
“…The results of this study indicate that job satisfaction is not always have larger influence with indirect effect in increasing the commitment of members of the organization in terms of affective, continuance and normative commitment. The results of this study are not consistent with previous studies (Brockner et al, 2006;Ma et al, 2018;Chan and Lai, 2017;Harris et al, 2018;Klotz et al, 2018).…”
Section: Resultscontrasting
confidence: 99%
“…The results of this study indicate that job satisfaction is not always have larger influence with indirect effect in increasing the commitment of members of the organization in terms of affective, continuance and normative commitment. The results of this study are not consistent with previous studies (Brockner et al, 2006;Ma et al, 2018;Chan and Lai, 2017;Harris et al, 2018;Klotz et al, 2018).…”
Section: Resultscontrasting
confidence: 99%
“…Having controlled for age and gender in line with previous studies (Chattopadhyay, 1999;Kidder, 2002;Klotz et al, 2018), our finding revealed a significant relationship between these two demographic variables and OCB. This is particularly important because it informs the researcher of the influence which these controlled variables had on this study.…”
Section: Discussionsupporting
confidence: 83%
“…In line with studies on OCB (Chattopadhyay, 1999;Kidder, 2002;Klotz, Bolino, Song, & Stornelli, 2018), the current study controlled for age and the gender of respondents as they may confound the findings of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Ketvirtoji pilietišką elgesį vertina vienu apibendrintu rodikliu, kuris susieja įvairias elgesio formas (pavyzdžiui, Joireman, Kamdar, Daniels, & Duell, 2006). Naujausiuose tyrimuose (Klotz, Bolino, Song, & Stornelli, 2018) pristatoma dar viena pilietiško elgesio tyrimų galimybė -profilių nustatymas. Autoriai, įvertinę darbuotojų pilietinį įsitraukimą, sąmoningumą, pakantumą, pagarbą, altruizmą, sudarė pilietiško elgesio profilius, pagal kuriuos darbuotojai buvo suskirstyti į penkias grupes (prosocialūs, padedantieji, specialistai, nuosaikieji ir neįsitraukę).…”
unclassified
“…Ng & Feldman (2008) nustatė, kad vyresnio amžiaus darbuotojai dažniau elgiasi pilietiškai, palyginti su jaunesniais kolegomis, tačiau Dirican ir Erdil (2016) tyrimu gavo, kad į darbuotojus nukreipto pilietiško elgesio raiška nesiskiria, lyginant darbuotojus, kurių amžius yra iki 30 metų, su vyresniais. Statuso (pareigų) atžvilgiu nustatyta, kad vadovai yra stipriau įsitraukę į pilietišką elgesį, palyginti su nevadovaujančiais darbuotojais, tačiau taip yra ne todėl, kad asmuo turi aukštesnes pareigas, o todėl, kad greičiau karjeros laiptais kyla darbuotojai, kurie aktyviau demonstruoja pilietišką elgesį (Klotz et al, 2018). Be abejo, pilietiško elgesio raiškos skirtumai, priklausantys nuo pareigų ir demografinių charakteristikų, yra nulemti konkrečių lyginamoms grupėms būdingų elgesio motyvų, veiklos pobūdžio ar kitų imties specifiką apibūdinančių veiksnių.…”
unclassified